Concerned about COVID-19 and the athletic heart? Prof Jon Drezner gives insight - Drezner, J. (BMJ talk medicine, 2020)
Are you involved in the care of athletes, and now planning their return to sport? Have you fully considered their cardiac health, especially in those with suspected/confirmed novel coronavirus infection? In this 15-minute podcast with Prof Jon Drezner, one of the world`s leading Sports Cardiologists & Team Physicians, we dive into some case-studies and some of the emerging evidence in this interesting area.